Multikulturalisme dalam Konteks GKI di Tanah Papua - Matulessy, Patricia Tripani; Rumahuru, Yance.Z.; Sopakua, Samel (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the role and challenges of the Evangelical Christian Church (GKI) in Tanah Papua in managing the high cultural and ethnic diversity in the region. As one of the largest religious institutions in Papua, GKI plays a strategic role in promoting social cohesion in a multicultural society. Using a qualitative approach and case study, this study explores GKI's church practices in embracing diversity through in-depth interviews, participant observation, and document analysis. The results show that GKI has carried out various forms of inculturation in liturgy and services, and adopted an inclusive theological approach to facilitate social integration amidst the diversity of the congregation. However, challenges remain, such as strong tribal identities, tensions in leadership, and cultural gaps between congregation members. GKI responds to these challenges through multicultural theological education, internal mediation, and affirmation of the values ​​of unity in Christ. This study concludes that GKI Tanah Papua is a contextual example of a church that seeks to live out the Christian faith in a complex and pluralistic social reality.